Migrant and refugee students’ right to linguistic education: Sociopolitical, sociolinguistic and educational reflections on Brazilian and German cases - Friedrich, Tatyana; Melo-Pfeifer, Sílvia; Ruano, Bruna (Education Policy Analysis Archives, 2021)
In this contribution, we reflect upon migrants’ right to linguistic education as a specific dimension of their right to education. Based on the Linguistic Human Rights approach (Skutnab-Kangas & Phillipson, 1995; also Hamel, 1995; Oliveira, 2003), we will argue that migrant and refugee students should see their right to linguistic education acknowledged in parallel to their right to education. Based on bibliographic and documentary research, we use the deductive and, mainly, the comparative method, in order to analyze the similarities and differences between individuals, phenomena and facts involved. Since the migrant and refugee school population is extremely heterogeneous, from a linguistic and cultural perspective, we will reflect upon concrete language policies and practices that can be developed in the Brazilian and German contexts in order to ensure the right to linguistic education. We argue that the implementation of pluralistic approaches to language learning and teaching might be a pedagogical tool to assure that right.